Answer with Step-by-step explanation:
Let a mass weighing 16 pounds stretches a spring
feet.
Mass=![m=\frac{W}{g}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7BW%7D%7Bg%7D)
Mass=![m=\frac{16}{32}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B16%7D%7B32%7D)
![g=32 ft/s^2](https://tex.z-dn.net/?f=g%3D32%20ft%2Fs%5E2)
Mass,m=
Slug
By hook's law
![w=kx](https://tex.z-dn.net/?f=w%3Dkx)
![16=\frac{8}{3} k](https://tex.z-dn.net/?f=16%3D%5Cfrac%7B8%7D%7B3%7D%20k)
![k=\frac{16\times 3}{8}=6 lb/ft](https://tex.z-dn.net/?f=k%3D%5Cfrac%7B16%5Ctimes%203%7D%7B8%7D%3D6%20lb%2Fft)
![f(t)=10cos(3t)](https://tex.z-dn.net/?f=f%28t%29%3D10cos%283t%29)
A damping force is numerically equal to 1/2 the instantaneous velocity
![\beta=\frac{1}{2}](https://tex.z-dn.net/?f=%5Cbeta%3D%5Cfrac%7B1%7D%7B2%7D)
Equation of motion :
![m\frac{d^2x}{dt^2}=-kx-\beta \frac{dx}{dt}+f(t)](https://tex.z-dn.net/?f=m%5Cfrac%7Bd%5E2x%7D%7Bdt%5E2%7D%3D-kx-%5Cbeta%20%5Cfrac%7Bdx%7D%7Bdt%7D%2Bf%28t%29)
Using this equation
![\frac{1}{2}\frac{d^2x}{dt^2}=-6x-\frac{1}{2}\frac{dx}{dt}+10cos(3t)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%5Cfrac%7Bd%5E2x%7D%7Bdt%5E2%7D%3D-6x-%5Cfrac%7B1%7D%7B2%7D%5Cfrac%7Bdx%7D%7Bdt%7D%2B10cos%283t%29)
![\frac{1}{2}\frac{d^2x}{dt^2}+\frac{1}{2}\frac{dx}{dt}+6x=10cos(3t)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%5Cfrac%7Bd%5E2x%7D%7Bdt%5E2%7D%2B%5Cfrac%7B1%7D%7B2%7D%5Cfrac%7Bdx%7D%7Bdt%7D%2B6x%3D10cos%283t%29)
![\frac{d^2x}{dt^2}+\frac{dx}{dt}+12x=20cos(3t)](https://tex.z-dn.net/?f=%5Cfrac%7Bd%5E2x%7D%7Bdt%5E2%7D%2B%5Cfrac%7Bdx%7D%7Bdt%7D%2B12x%3D20cos%283t%29)
Auxillary equation
![m^2+m+12=0](https://tex.z-dn.net/?f=m%5E2%2Bm%2B12%3D0)
![m=\frac{-1\pm\sqrt{1-4(1)(12)}}{2}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-1%5Cpm%5Csqrt%7B1-4%281%29%2812%29%7D%7D%7B2%7D)
![m=\frac{-1\pmi\sqrt{47}}{2}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-1%5Cpmi%5Csqrt%7B47%7D%7D%7B2%7D)
![m_1=\frac{-1+i\sqrt{47}}{2}](https://tex.z-dn.net/?f=m_1%3D%5Cfrac%7B-1%2Bi%5Csqrt%7B47%7D%7D%7B2%7D)
![m_2=\frac{-1-i\sqrt{47}}{2}](https://tex.z-dn.net/?f=m_2%3D%5Cfrac%7B-1-i%5Csqrt%7B47%7D%7D%7B2%7D)
Complementary function
![e^{\frac{-t}{2}}(c_1cos\frac{\sqrt{47}}{2}+c_2sin\frac{\sqrt{47}}{2})](https://tex.z-dn.net/?f=e%5E%7B%5Cfrac%7B-t%7D%7B2%7D%7D%28c_1cos%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7D%2Bc_2sin%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7D%29)
To find the particular solution using undetermined coefficient method
![x_p(t)=Acos(3t)+Bsin(3t)](https://tex.z-dn.net/?f=x_p%28t%29%3DAcos%283t%29%2BBsin%283t%29)
![x'_p(t)=-3Asin(3t)+3Bcos(3t)](https://tex.z-dn.net/?f=x%27_p%28t%29%3D-3Asin%283t%29%2B3Bcos%283t%29)
![x''_p(t)=-9Acos(3t)-9sin(3t)](https://tex.z-dn.net/?f=x%27%27_p%28t%29%3D-9Acos%283t%29-9sin%283t%29)
This solution satisfied the equation therefore, substitute the values in the differential equation
![-9Acos(3t)-9Bsin(3t)-3Asin(3t)+3Bcos(3t)+12(Acos(3t)+Bsin(3t))=20cos(3t)](https://tex.z-dn.net/?f=-9Acos%283t%29-9Bsin%283t%29-3Asin%283t%29%2B3Bcos%283t%29%2B12%28Acos%283t%29%2BBsin%283t%29%29%3D20cos%283t%29)
![(3B+3A)cos(3t)+(3B-3A)sin(3t)=20cso(3t)](https://tex.z-dn.net/?f=%283B%2B3A%29cos%283t%29%2B%283B-3A%29sin%283t%29%3D20cso%283t%29)
Comparing on both sides
![3B+3A=20](https://tex.z-dn.net/?f=3B%2B3A%3D20)
![3B-3A=0](https://tex.z-dn.net/?f=3B-3A%3D0)
Adding both equation then, we get
![6B=20](https://tex.z-dn.net/?f=6B%3D20)
![B=\frac{20}{6}=\frac{10}{3}](https://tex.z-dn.net/?f=B%3D%5Cfrac%7B20%7D%7B6%7D%3D%5Cfrac%7B10%7D%7B3%7D)
Substitute the value of B in any equation
![3A+10=20](https://tex.z-dn.net/?f=3A%2B10%3D20)
![3A=20-10=10](https://tex.z-dn.net/?f=3A%3D20-10%3D10)
![A=\frac{10}{3}](https://tex.z-dn.net/?f=A%3D%5Cfrac%7B10%7D%7B3%7D)
Particular solution, ![x_p(t)=\frac{10}{3}cos(3t)+\frac{10}{3}sin(3t)](https://tex.z-dn.net/?f=x_p%28t%29%3D%5Cfrac%7B10%7D%7B3%7Dcos%283t%29%2B%5Cfrac%7B10%7D%7B3%7Dsin%283t%29)
Now, the general solution
![x(t)=e^{-\frac{t}{2}}(c_1cos(\frac{\sqrt{47}t}{2})+c_2sin(\frac{\sqrt{47}t}{2})+\frac{10}{3}cos(3t)+\frac{10}{3}sin(3t)](https://tex.z-dn.net/?f=x%28t%29%3De%5E%7B-%5Cfrac%7Bt%7D%7B2%7D%7D%28c_1cos%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2Bc_2sin%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2B%5Cfrac%7B10%7D%7B3%7Dcos%283t%29%2B%5Cfrac%7B10%7D%7B3%7Dsin%283t%29)
From initial condition
x(0)=2 ft
x'(0)=0
Substitute the values t=0 and x(0)=2
![2=c_1+\frac{10}{3}](https://tex.z-dn.net/?f=2%3Dc_1%2B%5Cfrac%7B10%7D%7B3%7D)
![2-\frac{10}{3}=c_1](https://tex.z-dn.net/?f=2-%5Cfrac%7B10%7D%7B3%7D%3Dc_1)
![c_1=\frac{-4}{3}](https://tex.z-dn.net/?f=c_1%3D%5Cfrac%7B-4%7D%7B3%7D)
![x'(t)=-\frac{1}{2}e^{-\frac{t}{2}}(c_1cos(\frac{\sqrt{47}t}{2})+c_2sin(\frac{\sqrt{47}t}{2})+e^{-\frac{t}{2}}(-c_1\frac{\sqrt{47}}{2}sin(\frac{\sqrt{47}t}{2})+\frac{\sqrt{47}}{2}c_2cos(\frac{\sqrt{47}t}{2})-10sin(3t)+10cos(3t)](https://tex.z-dn.net/?f=x%27%28t%29%3D-%5Cfrac%7B1%7D%7B2%7De%5E%7B-%5Cfrac%7Bt%7D%7B2%7D%7D%28c_1cos%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2Bc_2sin%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2Be%5E%7B-%5Cfrac%7Bt%7D%7B2%7D%7D%28-c_1%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7Dsin%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2B%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7Dc_2cos%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29-10sin%283t%29%2B10cos%283t%29)
Substitute x'(0)=0
![0=-\frac{1}{2}\times c_1+10+\frac{\sqrt{47}}{2}c_2](https://tex.z-dn.net/?f=0%3D-%5Cfrac%7B1%7D%7B2%7D%5Ctimes%20c_1%2B10%2B%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7Dc_2)
![\frac{\sqrt{47}}{2}c_2-\frac{1}{2}\times \frac{-4}{3}+10=0](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7Dc_2-%5Cfrac%7B1%7D%7B2%7D%5Ctimes%20%5Cfrac%7B-4%7D%7B3%7D%2B10%3D0)
![\frac{\sqrt{47}}{2}c_2=-\frac{2}{3}-10=-\frac{32}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B47%7D%7D%7B2%7Dc_2%3D-%5Cfrac%7B2%7D%7B3%7D-10%3D-%5Cfrac%7B32%7D%7B3%7D)
![c_2==-\frac{64}{3\sqrt{47}}](https://tex.z-dn.net/?f=c_2%3D%3D-%5Cfrac%7B64%7D%7B3%5Csqrt%7B47%7D%7D)
Substitute the values then we get
![x(t)=e^{-\frac{t}{2}}(-\frac{4}{3}cos(\frac{\sqrt{47}t}{2})-\frac{64}{3\sqrt{47}}sin(\frac{\sqrt{47}t}{2})+\frac{10}{3}cos(3t)+\frac{10}{3}sin(3t)](https://tex.z-dn.net/?f=x%28t%29%3De%5E%7B-%5Cfrac%7Bt%7D%7B2%7D%7D%28-%5Cfrac%7B4%7D%7B3%7Dcos%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29-%5Cfrac%7B64%7D%7B3%5Csqrt%7B47%7D%7Dsin%28%5Cfrac%7B%5Csqrt%7B47%7Dt%7D%7B2%7D%29%2B%5Cfrac%7B10%7D%7B3%7Dcos%283t%29%2B%5Cfrac%7B10%7D%7B3%7Dsin%283t%29)
Answer:
-13 = n - 4
Step-by-step explanation:
-13 is four less than a number n
so four less than n can be written as n - 4
-13 = n - 4
n= -9
Answer:
Step-by-step explanation:
2x²+7x=-3
2x²+7x+3=0
2x²+x+6x+3=0
x(2x+1)+3(2x+1)=0
(2x+1)(x+3)=0
x=-1/2,-3
so C
Answer:
For question 1 you can try dividing each of the value
For instance, you can divide 9 by 25 and see if you get a nice number
e.g. 1/8=0.125, numbers like these
For the second question, you can find the fraction by dividing 1000 starting with the decimal points
e.g 0.650, you would be plotting 650/1000 and you would simplify the fraction to the lowest value any value above the decimal point you can multiply by the denominator and add the nominator value to get your final answer.
Step-by-step explanation:
Answer:
tan β = ![\frac{8}{15}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B15%7D)
Step-by-step explanation:
tan β =
=
= ![\frac{8}{15}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B15%7D)